Pelatihan Perencanaan Keuangan bagi Siswa Kelas XI di SMA Koperasi Pontianak - Rizal, Maulana Filani; Dami, Dami; Wibowo, Irvan (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This activity was motivated by the low level of understanding and skills among high school students in managing personal finances, which may hinder their preparedness to face future financial challenges. School cooperatives, as platforms for student economic activities, play a strategic role in enhancing students’ financial literacy and planning capabilities. The primary objective of this program was to provide effective financial planning training, enabling students to manage their personal finances wisely and prepare for a better future. The method employed was a participatory training approach, actively involving students in both theoretical and practical sessions, including budgeting, saving, and basic investing. Data were collected through pretest and posttest questionnaires to measure the improvement in students’ understanding, as well as through observations during the training sessions. The results showed a significant improvement in students’ financial knowledge and skills, as evidenced by an increase in the average percentage of correct answers from 67% in the pretest to 84% in the posttest. Therefore, the training proved effective in equipping students with fundamental financial management skills that support their independence and readiness for future financial responsibilities.